The 2014 Budget Act: Selected Legal Aspects - Andrzej Borodo (Prawo Budżetowe Państwa i Samorządu, 2014)
The Budget Act for the year 2014 raises legal questions in the context of the provisions of the Constitution as well as the Public Finance Act from 2009. Polish constitutional provisions relating to the state budget may be described as too general. They specify the requirements with regard to the Budget Act only to a limited extent.